Study on the dimensional stability of modern impression materials - Bogdan Mihai Gălbinașu; Marin-Lucian Dragason; Vlad-Cristian Grigore; Lucian Toma Ciocan; Ion Pătrașcu (Amaltea Medical Publishing House, 2020)
Objective. Comparative evaluation of the accuracy and dimensional stability of modern impression materials, given that often the casting is not done at a short interval after impression. Materials and methods. 4 modern impression materials were studied as follows: alginate (Tropicalgin-Zhermack), condensing silicone (Speedex-Coltene), addition silicone (Elite-Zhermack) and polyether (Impregum-3M/ESPE). With each of them was taken an impression of the same occlusal surface of an extracted molar, using a monophase technique . Both the control and the samples of impression materials obtained were subjected to stereomicroscopy investigations. Each sample was analyzed immediately (one hour after the impression), one day, 3 days and 7 days after the impression, respectively, taking the same reference marks for measurements identical to those on the control sample. Following the analysis, the dimensional variation of the analyzed materials compared to the control sample could be measured. The thickness of an enamel ridge bordered by two imagistically obvious ditches was taken as a reference. Results. Alginate suffers the greatest contraction at 24 hours (1.94%), but also at 7 days (0.91%). Addition silicones have the lowest shrinkage at 24 hours (0.03%) and polyethers the smallest variation over time (0.25% at 24 hours and 0.53% at 7 days). The polyethers also show the highest accuracy, the initial value (2,799 µm) being the closest to the value of the control sample (2,805 µm). Conclusions. All the impression materials studied undergo dimensional variations, the maximum contraction being in the first 24 hours, followed by a slight expansion due to postpolymerization de-stressing. Addition silicones show the lowest volumetric variation one day after registration, and polyethers 7 days after. Polyethers have the highest accuracy, while irreversible hydrocolloids have major dimensional changes and low accuracy compared to other materials.